Rufus Woods, the Columbia River & the building of modern Washington - Ficken, Robert E. (Washington State University Press, 1995)
Rufus Woods, for more than forty years the publisher of the Wenatchee Daily World, has often been called the "High Priest of the Columbia River." No person deserves the title more. From the editorial platform of the World, Woods tirelessly promoted Wenatchee and north central Washington. For decades he pegged his brightest hopes for the region's future on a huge Columbia River dam in the isolated Grand Coulee region. From 1918 through Grand Coulee's completion in 1941, Woods enthusiastically promoted the largest dam-building project in American history.